(untitled) (Journal of Universal Science Research, 2025)
Diplomatic discourse is studied in linguistics as a complex form of communication in global politics. The scientific and theoretical research in this field focuses on analyzing the linguistic structures, pragmatic features, and the role of diplomatic discourse in its socio-cultural context. Typically, diplomatic discourse is a special form of official communication, aimed at ensuring mutual understanding, conducting negotiations, and managing international relations. In this type of discourse, specific linguistic characteristics such as caution in speech, the subtlety of diplomatic language, conflict mitigation, and adaptation to social and political contexts are given particular attention. Studying diplomatic discourse also provides a deeper understanding of how language is used in political and cultural processes, communication strategies, and the role of language in global communication.